(untitled) (Contemporary Central & East European Law, 2024)
One of the problems addressed in Stanisław Kasznica’s work was the importance of administrative court rulings in the process of interpreting administrative law. In order to illustrate this in the current state of the law, judgments of administrative courts – the RAC and the HAC – were selected in cases involving complaints against decisions of provincial governors upholding decisions of heads of the civil registry office refusing to transcribe the birth certificate of a child in which people of the same sex were indicated as parents, as well as a specific resolution of a panel of seven judges of the HAC of 2 January 2019, II OSK 1/19.